Comparative Analysis of LIS Curriculum Structure Based on IFLA Standards: A Study of Islamic and General Universities in Indonesia - Arwendria, Arwendria; Fadli, M; Batubara, Hadad Alwi (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2026)
Background: As global standards for Library and Information Science (LIS) education become increasingly standardized, institutions must balance international benchmarks with localized identities. In Indonesia, this tension is particularly evident when comparing the curricular structures of Islamic and non-Islamic universities against the 2022 IFLA Guidelines. Purpose: This study investigates the degree of alignment between Indonesian LIS curricula and IFLA core competency areas, specifically examining whether institutional religious identity (Islamic vs. non-Islamic) creates significant differences in credit allocation across foundational and technical domains. Methods: Using a quantitative, ex post facto design, the researchers analyzed the official curricula of 26 accredited LIS programs (13 Islamic and 13 non-Islamic). Variables included credit unit weights for IFLA Core Areas 1 (Foundations), 2 (Technical & Management), and 3 (User Services), with a specific focus on Ethics and Professionalism (FKA8). Data were analyzed using descriptive statistics, independent samples t-tests, and cluster analysis. Findings: The study reveals significant structural convergence between both institution types, with Core Area 2 (Technical & Management) dominating all curricula. Statistical analysis showed no significant difference in the emphasis on Ethics (FKA8) or Foundations (Core 1). However, a significant difference was identified in Core Area 2, where Islamic universities allocated a higher proportion of credits compared to their non-Islamic counterparts. Originality/Value: The results suggest that the "distinctive character" of Islamic LIS programs may reside in implicit pedagogy and value integration rather than formal quantitative structures. This study provides critical empirical evidence for accreditation bodies and curriculum developers, highlighting the nuanced interplay between global IFLA standards and local institutional identities.